2020
DOI: 10.3390/ijerph17207437
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life after Spinal Cord Injury: A Multiple Case Study Examination of Elite Athletes

Abstract: A three-times World Champion in BMX (an acronym for Bicycle Motocross) dirt jumps, a Junior World Champion in ski jumping, and a European karate Champion sustained spinal cord injuries at the cervical and thoracic level. Such a severe trauma is tantamount to the end of a professional sporting career. In such a situation, the athlete’s life significantly changes in every aspect of it: health, professional, and social. The greatest sports champions have not yet been portrayed in the context of a strategy they us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 37 publications
0
3
0
2
Order By: Relevance
“…Although other studies previously reported benefits of sports participation for athletes with disabilities (Diaz et al, 2019;Goraczko et al, 2020;Mendonça et al, 2017;Oh;So, 2022;Peacock et al, 2019), the comparison of QoL between sports participants and non-participants have been poorly studied. The present research included a considerably larger sample of volunteers than the samples used in previous studies, used pairing criteria of the samples, and the results demonstrated the importance at the para-athletics participation on QoL among high performance athletes and amateur athletes with physical disabilities.…”
Section: Recima21 -Revistamentioning
confidence: 99%
“…Although other studies previously reported benefits of sports participation for athletes with disabilities (Diaz et al, 2019;Goraczko et al, 2020;Mendonça et al, 2017;Oh;So, 2022;Peacock et al, 2019), the comparison of QoL between sports participants and non-participants have been poorly studied. The present research included a considerably larger sample of volunteers than the samples used in previous studies, used pairing criteria of the samples, and the results demonstrated the importance at the para-athletics participation on QoL among high performance athletes and amateur athletes with physical disabilities.…”
Section: Recima21 -Revistamentioning
confidence: 99%
“…Most of our understanding of the regeneration after SCI derives from experimental studies performed on well-characterized SCI models, which do not precisely reflect the variability of human SCI pathology. Recent studies addressing differences between athletes and nonathletes with SCI focus mainly on the mental health and overall quality of life [60,61]. The results indicate that people participating in sport activities appropriate to their degree of disability have a significantly higher quality of life and life satisfaction compared to people not involved in any sport.…”
Section: Physical Activity Applied Before Sci Induced Glial and Axona...mentioning
confidence: 99%
“…Oft sind diese Patient*innen im erwerbsfähigen Alter, Familienväter oder -mütter sowie Jugendliche oder Kinder. Darüber hinaus führt eine wesentlich längere Pflegezeit zu schweren finanziellen Verpflichtungen für Familie und Staat [5].…”
Section: Einführungunclassified
“…Häufig sind dies Patient*innen im erwerbsfähigen Alter, Familienväter oder -mütter sowie Jugendliche oder Kinder. Die Tragweite sowohl auf persönlicher als auch auf sozioökonomischer Ebene ist enorm [5].…”
Section: Ergebnisseunclassified